A study of on-line payment awareness in Terengganu: a case of e-services offered by government / Mimi Zazira Hashim, Roziana Ahmed and Mohd Khirzan Badzli Abd Rahman - Hashim, Mimi Zazira; Ahmed, Roziana; Abd Rahman, Mohd Khirzan Badzli (2008)
This paper aims to come out with comprehensive study of online payment awareness provided by Malaysia Government in Terengganu. Services in Malaysia are adopting e- service in order to enhance their services. At the moment, an e-service portal had been developed to be used by Malaysia citizen over the Internet. In fact, this study attempts to discover why this issue arises in transforming the service from traditional to digital system. This study helps us to determine the elements of online payment that gives great impacts to the government servants who were the respondents that represent the public in Terengganu. Overall findings of study indicate that the majority of the publics are IT literate and they have experienced using the Internet. The study has shown that at least the publics have equipped themselves with the first ability to use the Internet to get information. The respondents also preferred to use computers in their offices to access to the Internet. It was found that the majority of the respondents admitted that they knew about the services offered. Through the study, television was ranked the first as an information channel of online services. It is only a few of the respondents reported of having experience with the online services. The study also investigates the reasons for the publics reluctant to use online service offerings. The findings also indicate that the publics’ awareness on the government online services is still at the minimal level. Based on the overall results, it can be concluded that the awareness of online payment is still at the unsatisfactory level. The publics are aware on certain services but ignorance on other services. The phenomena exist because the information on some services has been extensively disseminated and has reached the publics’ knowledge through various media; printed or electronic, formal or informal.